IMPLEMENTASI PENDEKATAN DEEP LEARNING DI SDN PENGAMBANGAN 6 BANJARMASIN - Anggriani, Rifka; Abidinsyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Basic education is a critical foundation in shaping childrens’s character and competence. This study aims to describe teachers’ understanding of the deep learning approach, describe the implementation of the deep learning, learning process, and identify the obstacles encountered during the implementation of the deep learning approach at SDN Pengambangan 6 Banjarmasin. This study used a descriptive qualitative approach. Data were collected through interviews, observation, and documentation involving the principal, class teachers of grades III, IVA, IVB, and V, and students form those classes. Data were analyzed using the Miles and Huberman technique through data reduction, data display, and verification, while data validity was tested through souce and technique triangulation. The result show that: (1) the principal and class teachers already have a good understanding of the deep learning approach, particulary the concepts of mindful learning, meaningful learning, and joyful learning; (2) the implementation of the deep learning approach has been carried ou through learning that builds student awareness, connects material with daily life, and creates and enjoyable learning atmosphere, supported by various learning models, media, and technology; and (3) the obstacles faced include suboptimal parental involvement, teachers’ limited skills in designing learning, the diversity of student characteristics, time constraints, and limited technology and internet facilities. Nevertheless, the school continues to strive to improve teacher competence, strengthen cooperation with parents, and optimize learning facilities.